Redo Laparoscopic Pyeloplasty in Infants and Children: Feasible and Effective - Al-Hazmi, Hamdan; Peycelon, Matthieu; Carricaburu, Elisabeth; Manzoni, Gianantonio; Neel, Khalid Fouda; Ali, Liza; Grapin, Christine; Paye-Jaouen, Annabel; El-Ghoneimi, Alaa (Frontiers in Pediatrics, 2020)
Purpose. To determine the feasibility and effectiveness of redo laparoscopic pyeloplasty among patients with failed previous pyeloplasty, specifically examining rates of success and complications. Materials and Methods. We retrospectively reviewed the charts of all patients, who underwent redo laparoscopic pyeloplasty from 2006 to 2017. This included patients who underwent primary pyeloplasty at our institution and those referred for failures. Analysis included demographics, operative time, complications, length of hospital stay, complications, and success. Success was defined as improvement of symptoms and hydronephrosis and/or improvement in drainage demonstrated by diuretic renogram, especially in those with persistent hydronephrosis. Descriptive statistics are presented. Results. We identified 22 patients who underwent redo laparoscopic pyeloplasty. All had Anderson-Hynes technique except two cases in which ureterocalicostomy was performed. Median (IQR) follow-up was 29 (2-120) months, median time between primary pyeloplasty and redo laparoscopic pyeloplasty was 12 (7-49) months. The median operative time was 200 (50-250) minutes, and median length of hospital stay was 3 (2-10) days. The procedure was feasible in all cases without conversion. During follow-up, all but two patients demonstrated an improvement in the symptoms and the degree of hydronephrosis. 91% of patients experienced success and no major complications were noted. Conclusions. Redo laparoscopic pyeloplasty is feasible and effective with a high success rate and low complication rate.